Benefit - Cost Analysis of Agro-forestry Trees in Eroded Soils - a Case Study of Upper - Swan Catchment in District Una (H.P.) - Rana, Rajesh K.; Kaushal, P.; Negi, Y. S. (Indian Forester, 2000)
Establishment of successful agro-forestry plantations in fragile eco-systems such as eroded soils is a difficult job as it involves relatively higher cost and generates less returns. Site specific benefit-cost studies for plantations on such sites thus are important. The present study was undertaken in the Upper-Swan river catchment area of Una District in Himachal Pradesh. This catchment area is peculiar for its eroded soils. Tree species, Dalbergia sissoo, Albizia lebbek; Toona ciliata and Grewia optiva were considered for analysis. Plantations being sparse the calculations were done on per 100 tree basis at relatively higher (12%) rate of returns. Results indicated that the plantations under consideration were profitable as both, Net Present Worth (NPW) and the Benefit. Cost ratio (B.C ratio) criteria testify it. Grewia optiva being very popular and useful fodder species of the area, yielded the highest NPW (Rs.11,644) followed by Dalbergia sissoo (Rs.5,611), Toona ciliata (Rs.5,155) andAlbizia lebbek (Rs.3,350). However, the B.C ratio was found to be the highest for Dalbergia sissoo (2.59) followed by Toona ciliata (2.58), Grewia optiva (2.35) and Albizia lebbek (1.97).